Corporate bodies and guilty minds the failure of corporate criminal liability - Laufer, William S. (Univ.of Chicago Press, 2006)
"In this timely work, William S. Laufer argues that even with recent legal reforms - and those about to be enacted - corporate criminal law continues to be ineffective. Corporate Bodies and Guilty Minds outlines the many reasons why this is so. Laufer considers the failure of courts and legislatures to fashion liability rules that fairly attribute blame for organizations. He analyzes the games that corporations play to deflect criminal responsibility. And he also demonstrates how the exchange of cooperation for prosecutorial leniency and amnesty belies true law enforcement. But none of these factors, according to Laufer, trumps the fact that there is no single constituency or interest group that strongly and consistently advocates the importance and priority of corporate criminal liability. In the absence of a new standard of corporate liability, the power of regulators to keep corporate abuses in check will remain insufficient"